A relational model of career adaptability and career prospects: The roles of leader–member exchange and agreeableness. Issue 2 (12th December 2019) - Yang, Xuhua; Guan, Yanjun; Zhang, Yejun; She, Zhuolin; Buchtel, Emma E.; Mak, Miranda Chi Kuan; Hu, Hanlin
Abstract : Drawing on career construction theory and leader–member exchange (LMX) theory, this research examined the mediating role of LMX in explaining the effect of employee career adaptability on career prospects, as well as the moderating role of agreeableness in this process. Two field studies were conducted among Chinese employees and their supervisors to test this model. In study 1, time‐lagged multisource data were collected from 252 employees and 69 supervisors. The results showed that supervisor‐rated LMX (Time 2) mediated the relationship between employee‐rated career adaptability (Time 1) and supervisor‐rated career prospects (Time 2). In study 2, a cross‐lagged panel study among 149 employees and 47 supervisors across 4 months replicated the mediating effect of LMX for the relationship between career adaptability and career prospects. Results of study 2 also showed that LMX (Time 1, supervisor‐rated) did not significantly predict career adaptability (Time 2, employee‐rated), providing support for the unidirectional relationship from career adaptability to LMX in this context. The moderating role of agreeableness was supported such that the effect of career adaptability on LMX, as well as the indirect effect of career adaptability on career prospects via LMX, was stronger among employees with a higher level of agreeableness. We discussed the theoretical and practical implications of these findings and offered directions for future research. Practitioner points: Organizations should consider using career adaptability as an important tool to select high‐potential job candidates, provided that other more important selection criteria have been met, since employees with a higher level of career adaptability are more capable of building high‐quality relationships with their supervisors and receiving positive recommendations from them. Organizations should also help employees to recognize the important role of agreeableness in their work, in order to maximize the potential benefits of career adaptability on employees' career development; otherwise employees' career prospects will be constrained even if they have a high level of career adaptability.